Grazing increases the concentration of CLA in dairy cow milka - M.N. Lahlou (Animal, 2014)
An experiment was conducted to examine whether increased CLA in milk of dairy cows fed fresh pasture compared with alfalfa and corn silages was because of ruminal or endogenous synthesis. Eight Holsteins were fed a total mixed ration using alfalfa and corn silages as the forage source in confinement or grazed in a replicated crossover design. The proportion of total fatty acids as CLA (primarily c9, t11-18:2) in g/100 g was 0.44 v. 0.28 in ruminal digesta, 0.89 v. 0.53 in omasal digesta and 0.71 v. 1.06 in milk during confinement feeding and grazing, respectively. Blood plasma CLA was 0.54 v. 1.05 mg/l for the two treatments, respectively. The increased concentration of CLA in milk with grazing likely resulted from increased synthesis through desaturation of t11-18:1 in the mammary gland.